Protein Microarrays: A New Tool for the Study of Autoantibodies in Immunodeficiency - Rosenberg, Jacob M.; Utz, Paul J. (Frontiers in Immunology, 2015)
Autoimmunity is highly coincident with immunodeficiency. In a small but growing number of primary immunodeficiencies, autoantibodies are diagnostic of a given disease and implicated in disease pathogenesis. In order to best gain an understanding of the role of autoantibodies in immunodeficiencies and to discover novel autoantibodies, new proteomic tools are needed. Protein microarrays have the ability to screen for reactivity to hundreds to many thousands of unique autoantigens simultaneously on a single chip using minimal serum input. Here, we review the different types of protein microarrays and how they can be useful in framing the study of primary and secondary immunodeficiencies.